Kesejahteraan Psikologis dalam Menghadapi Ketahanan Pangan - Hidayat, Novi; Ikromi, Ziyadi Ali; Rismawati, Rismawati; Widyautami, Putri Ayu; Maulana, Iksal (Universitas Pahlawan Tuanku Tambusai, 2025)
Food security encompasses not just the availability and accessibility of food, but is also intricately linked to the psychological well-being of the community. This community service initiative seeks to enhance understanding and awareness among urban populations, particularly in the Jakarta region, about the connection between food security and mental health. The program employs an educational and participatory methodology that engages a variety of stakeholders, including academics, food distribution organizations, consumer advocacy groups, and local residents. Key activities include workshops, discussions on food policy, and education regarding the significance of emotional stability and a sense of security in obtaining sufficient food. The outcomes of this initiative indicate that the community's comprehension of the psychological dimensions of food security remains limited; however, there is considerable enthusiasm for incorporating a mental well-being perspective into food policies and initiatives. This program aspires to serve as a collaborative model for developing a food system that is not only sustainable in physical and economic terms but also fosters the overall mental well-being of the community.